2013
DOI: 10.1007/s11262-013-0978-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of canine influenza A virus (H3N2) in Thailand

Abstract: In January 2012, several clinical cases of dogs with flu-like symptoms, including coughing, sneezing, nasal discharge, and fever, were reported in a small-animal hospital located in Bangkok, Thailand. One influenza A virus was identified and characterized as an avian-like influenza virus H3N2. The virus was named A/canine/Thailand/CU-DC5299/12. A phylogenetic analysis indicated that the canine virus belonged to an avian Eurasian lineage and was genetically related to the canine influenza viruses H3N2 from Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 32 publications
1
47
0
1
Order By: Relevance
“…Since the discovery of H3N2 CIV in 2007, most studies have focused on the genetic and virological characterization of individual isolates (6, 16, 18-21, 23, 25, 26) and on clinical and epidemiological investigations (20,(22)(23)(24). Here we compiled all the publicly available complete genome sequences of CIV and carried out a comprehensive phylogenetic analysis to elucidate its evolutionary history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of H3N2 CIV in 2007, most studies have focused on the genetic and virological characterization of individual isolates (6, 16, 18-21, 23, 25, 26) and on clinical and epidemiological investigations (20,(22)(23)(24). Here we compiled all the publicly available complete genome sequences of CIV and carried out a comprehensive phylogenetic analysis to elucidate its evolutionary history.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, H3N2 CIVs have often been isolated in dogs in both China and South Korea, indicating that this virus is stably circulating in the Asian canine population (18)(19)(20)(21)(22). Moreover, the geographical distribution of this virus is rapidly expanding, as it has also been isolated in dogs in Thailand (23). Notably, H3N2 CIV seems to have a broad host range, as it has been isolated from cats during an outbreak of respiratory disease in a shelter in South Korea (24,25), and experimental studies have shown that H3N2 CIV can infect ferrets, although transmission in this species seems to be limited (26).…”
mentioning
confidence: 99%
“…While there was evidence of additional EIV transmission events into dogs in the United States,6 there was no evidence of sustained transmission of these other events, nor were there reports of CIV transfer back to horses or to humans 7. An H3N2 avian influenza virus (AIV) was detected in dogs in Asia in ~2005 and now appears to be endemic 8, 9, 10, 11. H3N2 subtype viruses are endemic in swine.…”
Section: Introductionmentioning
confidence: 99%
“…The H3N2 CIV most likely arose around 2005 or 2006 in China but was first recognized in South Korea around the same time, and the virus or specific antibodies have since been detected in many parts of China and Korea, as well as Thailand (41)(42)(43)(44). The epidemiology of the H3N2 CIV is still poorly understood, but some reports indicate moderate seroprevalence in some household dog populations, and it has been transferred over long distances both within and between the three countries in which has been detected (45).…”
mentioning
confidence: 99%
“…Populations of farmed dogs may play a role in the maintenance of the virus (46). H3N2 CIV is an avian virus-like strain, and all isolates share a single common ancestor, but the circumstances of the transfer are unknown, and its gene segments are related to both Eurasian and American avian influenza virus lineages (42,47). H3N2 CIV appears to have a relatively broad host range, and the virus naturally infects cats and spreads among them under some circumstances (48).…”
mentioning
confidence: 99%